Isolation and Identification of Dermatophytes from Toenails and Interdigital Spaces of Students Using Czapek Yeast Extract Agar - Lisa Savitri; Kharisul Ihsan; Rochmad Krissanjaya; Elfred Rinaldo Kasimo; Novirma Yanti; Mochamad Hanif Hilmi (Biology, Medicine, & Natural Product Chemistry, 2025)
Dermatophytosis remains a common superficial fungal infection affecting nails and interdigital spaces, with Trichophyton rubrum and T. mentagrophytes as the predominant etiologic agents. The recent emergence of terbinafine-resistant T. indotineae has raised new challenges in diagnosis and treatment. Although Sabouraud Dextrose Agar is the conventional medium for fungal culture, alternative media such as Czapek Yeast Extract Agar (CYA) may provide additional advantages for dermatophyte isolation and morphological identification. This study aimed to isolate and identify dermatophytes from toenails and interdigital spaces of university students using CYA medium and to evaluate its applicability in dermatophyte culture. A cross-sectional descriptive study was conducted among 100 university students aged 18–24 years. Specimens were collected from toenails (n = 60) and interdigital spaces (n = 40). Direct microscopy was performed using 20% KOH preparation. Samples were cultured on CYA supplemented with chloramphenicol and cycloheximide, and incubated at 28 ± 2 °C for up to 21 days. Fungal isolates were identified based on macroscopic and microscopic morphology. Data were analyzed descriptively, and associations were tested using the chi-square test. Fungal elements were detected in 65% of samples by KOH examination, and dermatophyte growth was confirmed in 52% of cultures. The most frequently isolated species were T. rubrum (28%) and T. mentagrophytes (18%). Notably, T. indotineae was detected in 5% of samples. No significant difference was found between toenail and interdigital isolates (p = 0.26). Dermatophytes are prevalent among university students, with T. rubrum as the dominant species. The detection of T. indotineae highlights its emerging role in young populations. CYA proved effective for dermatophyte isolation and may serve as an alternative culture medium in academic and diagnostic laboratories.